Recent study of transition bimetallic catalyst in biomass tar steam reforming for hydrogen-rich syngas: A comprehensive bibliometric analysis - Mohamad Jamil Arif, Mansor; Irna Haslina, Ibrahim; Asmida, Ideris; Wantala, Kitirote; Nguyen, Van Cuong; Sumaiya, Zainal Abidin (Elsevier Ltd., 2025)
An increase in the human population and the energy crisis have gained global attention in the search for alternative energy resources. Biomass energy has garnered significant attention as a sustainable alternative to fossil fuels, which can reduce greenhouse gas emissions and mitigate carbon footprints. The usage of biomass energy shows certain challenges and problems, such as tar formation. In order to understand this issue, a catalytic steam reforming of biomass tar has been carefully investigated. However, this process still faces several complications, such as catalyst deactivation, coke deposition, and other operational challenges, which require further research and improvement. This study employs a bibliometric analysis conducted from 1997 to 2024, pointing out keywords, nations, journals, inter-country co-authorship networks, and co-occurrence visualisations. The judgement was carried-out by utilising the Scopus database® and further demonstrated through R-Studio and VOSviewer. This inclusive literature review provides a thorough and up-to-date overview of the research on catalytic steam reforming of biomass tar. This question brings out the critical role of bimetallic catalysts and the need for continued invention in this field to address the global energy and environmental challenges.